2006
DOI: 10.1088/0268-1242/21/4/019
|View full text |Cite
|
Sign up to set email alerts
|

Strong sensitivity of photoluminescence of InAs/AlAs quantum dots to defects: evidence for lateral inter-dot transport

Abstract: The low-temperature steady-state and time-resolved photoluminescence (PL) from self-assembled InAs quantum dots (QDs) embedded in AlAs with various densities of growth-induced defects has been studied. In contrast to the system of InAs/GaAs QDs, a drastic decrease of the QD PL intensity and decay duration with the formation of relaxed dislocated clusters was observed. It is shown that this strong difference in the luminescence properties of the InAs/GaAs and InAs/AlAs QD systems arises from the very large exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
0
11
0
2
Order By: Relevance
“…However, when the InAs thickness exceeds the critical thickness, some QDs are larger than others and are strain relieved by lattice misfits, probably during the InGaAs covering or the initial GaAs covering. These dislocated QDs may attract indium adatoms from the nearby still strained QDs, 18,23 as indicated in Fig. 8(b).…”
Section: B Tem Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…However, when the InAs thickness exceeds the critical thickness, some QDs are larger than others and are strain relieved by lattice misfits, probably during the InGaAs covering or the initial GaAs covering. These dislocated QDs may attract indium adatoms from the nearby still strained QDs, 18,23 as indicated in Fig. 8(b).…”
Section: B Tem Analysismentioning
confidence: 98%
“…21,22 It has been reported that defects such as dislocations can be energetically favorable sites for indium migration. 18,23 Given sufficient kinetics, the dislocated QDs might affect the strain relieving process of the nearby not yet relaxed QDs. This suggests a more complicated strain relaxation process in the QDs.…”
Section: Introductionmentioning
confidence: 99%
“…The size and density of the lens-shaped QDs were measured by transmission electron microscopy, yielding an average diameter of 12 nm and a density of about 2×10 10 dots per cm 2 . The relatively low QD density prevents carrier redistribution between the QDs [13,14].…”
Section: Sample and Experimental Setupmentioning
confidence: 99%
“…При использованном нами нерезонансном возбуждении фотолюминесценции возможны два сценария, приводящих к уменьшению концентрации носителей заряда в СС и КТ при появлении дефектов -центров безызлучательной рекомбинации в матрице AlAs. Уменьшение концентрации носителей заряда захваченных в КТ и СС, из-за повышения темпа безызлучательной рекомбинации в матрице [22] Несмотря на то, что энергия активации гашения полосы СС (17 мэВ) в гетероструктуре InAs/AlAs/GaAs/Si близка к энергии активации гашения полосы КТ (20 мэВ), механизм температурного гашения не столь очевиден. Дело в том, что в СС гетероструктур, выращенных на согласованных подложках, гашение ФЛ при повышении температуры обусловлено термоактивацией в делокализованные состояния выше уровня протекания с последующим транспортом к локализованным в плоскости СС центрам безызлучательной рекомбинации [11].…”
Section: обсуждение результатовunclassified